Highly effective carbon-supported gold-ionic liquid catalyst for acetylene hydrochlorination. Issue 38 (15th July 2019) - Qi, Xueyan; Chen, Weifeng; Zhang, Jinli
Abstract : The sulfur-containing ionic liquid (IL) trimethylsulfonium iodide (C3 H9 SI) was used to synthesize an efficient non-mercuric catalyst with HAuCl4 ·4H2 O as a precursor and spherical active carbon (SAC) as a support. Abstract : The sulfur-containing ionic liquid (IL) trimethylsulfonium iodide (C3 H9 SI) was used to synthesize an efficient non-mercuric catalyst with HAuCl4 ·4H2 O as a precursor and spherical active carbon (SAC) as a support. Various Au-IL/SAC catalysts were synthesized using the incipient wetness impregnation technique and applied to acetylene hydrochlorination. The 0.3% Au-IL/SAC catalyst showed the best catalytic performance, with an acetylene conversion of 90% at a temperature of 170 °C and gas hourly space velocity (GHSV) of 360 h −1 using water as the solvent. The catalyst also displayed excellent long-term stability: C2 H2 conversion was maintained at 97% for up to 200 h ( T = 170 °C, GHSV = 90 h −1 ). Brunauer–Emmett–Teller surface area, thermogravimetric analysis, temperature programmed desorption, X-ray diffraction, transmission electron microscopy, and X-ray photoelectron spectroscopy results together showed that the C3 H9 SI additive significantly improved the dispersion of Au species and inhibited coke deposition on the catalyst surface during the acetylene hydrochlorination reaction. The superior activity and stability of the Au-IL/SAC catalyst make it a green catalyst for the industrial application of acetylene hydrochlorination.